2010
DOI: 10.2174/157016110791330852
|View full text |Cite
|
Sign up to set email alerts
|

The Rationale for Comparative Studies of Accelerated Atherosclerosis in Rheumatic Diseases

Abstract: The inflammatory pathogenesis of atherosclerosis is now well-established, owing to in vitro and in vivo studies and the application of high sensitivity assays for C-reactive protein (CRP) in the general population and specific groups at risk for cardiovascular disease (CVD). In view of the complexity of inflammation-induced atherosclerosis, the rationale for comparative studies of atherogenesis in rheumatic diseases with diverse inflammatory pathogenesis seems obvious; they are human in vivo models to study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 150 publications
0
47
0
3
Order By: Relevance
“…The drug of choice for the prevention of attacks and the development of amilodosis in patients with FMF is colchicine, which has anti-neutrophilic, anti-inflammatory, anti-fibrotic, and anti-proliferative effects (20). Preliminary data propose that enhanced atherogenesis may accompany FMF in the absence of a sufficient suppression of inflammation by colchicine (21). In our study, we found that stiffness measurements get higher in the attack period.…”
Section: Discussionmentioning
confidence: 99%
“…The drug of choice for the prevention of attacks and the development of amilodosis in patients with FMF is colchicine, which has anti-neutrophilic, anti-inflammatory, anti-fibrotic, and anti-proliferative effects (20). Preliminary data propose that enhanced atherogenesis may accompany FMF in the absence of a sufficient suppression of inflammation by colchicine (21). In our study, we found that stiffness measurements get higher in the attack period.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, since the lifestyle-related factors BMI [20], smoking [20] and alcohol use [21] have been suggested to affect levels of inflammatory markers, a two-step cluster analysis was performed to create a single variable from these lifestyle risk factors [22]. In model 2, we evaluated the effect of the chronic inflammation-relevant disorders rheumatoid arthritis [23] and coronary heart disease [24] together with the factors from model 1. These chronic disorders were also pooled into one variable in order to control the number of degrees of freedom in the analyses.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, it was reported that the prothrombotic pathways and atherosclerosis can be suppressed by using colchicine [5,6]. Platelet size is correlated with platelet function and activation.…”
Section: Introductionmentioning
confidence: 99%